Effective In-Vehicle Network Training Strategy for Automotive Engineers - Jin Young Byun; Jae Wan Park; Do Yeon Kim; Chang Young Jo; Jae Wook Jeon (IEEE Access, 2022)
This study describes a hands-on in-vehicle network (IVN) training course for automotive engineers, particularly for learners with different prior knowledge. We collected essential content to educate those with different backgrounds on IVN-related information, which is essential in practice. The course aims within a short period to effectively educate engineers working in the industry on IVN systems, and explains how to employ embedded systems and graphical user interfaces (GUIs) for this purpose. At the end of the training, the level of knowledge before and after training was compared to evaluate the training results, and engineers’ responses were recorded.